THE DILEMMA OF MUHAMMADIYAH IN ACEH AMIDST THE RELIGIOUS CONTESTATION BETWEEN WAHHABI AND ASWAJA: A Historical Parallelism - Muhammad Ridha Basri (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
The controversy and rejection surrounding the construction of the Muhammadiyah mosque in Bireuen have marked a new chapter in the history of Muhammadiyah in Aceh. Some studies suggest that this is a conflict between Muhammadiyah and traditional Islamic communities. This article presents a different argument, asserting that Muhammadiyah in Aceh has become an organization inadvertently drawn into a religious contestation between two religious communities: the Wahhabi and the Ahlu Sunnah wa Jamaah (Aswaja) groups. Muhammadiyah does not actually have a direct conflict with traditional Islam or the dayah community in Aceh, but it finds itself in a precarious situation when conflicts arise between these two groups. Muhammadiyah becomes entangled with one of these groups due to shared aspects in religious doctrine. The contestation between these two major currents is not only about the domination of doctrines and religious authority but also extends into the competition for access to economic and socio-cultural resources. This situation parallels and echoes the early history of Muhammadiyah in Aceh, where it was inadvertently involved in conflicts between uleebalang/teuku (local rulers) and ulama/teungku (traditional scholars). During that time, Muhammadiyah, allied with uleebalang, found itself confronting ulama.